Antioxidant Effect of a Dihydropyridine Calcium Antagonist Nitrendipine in Streptozotocin-Induced Diabetes (vol 57, pg 126, 2020) - Unuvar, S.; Gursoy, S.; Berk, A.; Kaymaz, B.; Ilhan, N.; Aktay, G. (Pleiades Publishing Ltd, 2021)
[Abstract Not Available]